Associations of Chronic Marijuana Use with Changes in Salivary Microbiome - Jun Panee; Yujia Qin; Youping Deng (Microorganisms)
The legalization of marijuana (MJ) for medicinal and recreational use has raised concerns about its potential impact on health, including oral health. While MJ use has been linked to poor oral health, its effects on the composition of the oral microbiome remain unclear. This cross-sectional study analyzed saliva samples from chronic MJ users (n = 18) and nonusers (n = 20) to investigate MJ-related changes in salivary microbiome composition. We identified significant differences in the relative abundance of 16 taxa, including seven species, such as Megasphaera micronucliformis, Prevotella melaninogenica, and Streptococcus anginosus. Additionally, five species showed positive correlations with cumulative lifetime MJ use, including Streptococcus vestibularis and Streptococcus parasanguinis. By grouping salivary microbial communities into clusters based on their association with periodontal health, we found that the cluster with species associated with poor periodontal health had the highest percentage of MJ users. Moreover, MJ use significantly contributed to variance in microbial communities in individuals with relatively good periodontal health. These findings suggest that chronic MJ use is associated with alterations in the salivary microbiome, highlighting its potential broader impact on oral and systemic health.